A novel approach to reduce both front and rear side power losses in PERC solar cells using different combinations of transparent metal oxides. Issue 2 (15th January 2023) - Ahmad, Waqas; Tahir, Sofia; Ali, Adnan; Mahmood, Khalid
Abstract: This paper aims to check the TMOs (transition metal oxides) influence on the front side passivation of c-Si PERC solar cells. This simulation work compares three different configurations with standard size c-Si wafers. Configuration (1) consists of SiNx /NiOx at the front and Al2 O3 /MoOx /SiNx at the rear, configuration (2) SiNx /WOx at the front side and Al2 O3 /MoOx /SiNx at the rear side, and configuration (3) SiNx /TiO2 at the front side and Al2 O3 /MoOx /SiNx at a rear side of c-silicon wafer simulated through Sunsolvesoftware. These configurations are selected after comparing the thickness effect of TMOs through the Wafer Ray tracer calculator. On the front side, thicknesses of NiOx, WOx, and TiO2 are tested, ranging from 10 nm to 100 nm, using a wafer ray tracer, from which the three best thicknesses are selected. All three selected configurations have an efficiency of 21.36%, 21.08%, and 20.95%, respectively. We have also compared all possible parameters such as reflections, absorptions, transmissions, open-circuit voltage, short circuit current, fill factor and efficiency.The front side losses were reduced due to TMO's thin layers. TMOs are used as transparent conductive oxide layers at the front side of the c-Si PERC solar cell to reduce the losses of the front side as supportive thin layers with ARC SiNx .